1995
DOI: 10.1523/jneurosci.15-03-02417.1995
|View full text |Cite
|
Sign up to set email alerts
|

Receptive-field properties of deafferentated visual cortical neurons after topographic map reorganization in adult cats

Abstract: When neurons in primary visual cortex of adult cats and monkeys are deprived of their normal sources of activation by matching lesions in the two retinas, they are capable of acquiring new receptive fields based on inputs from regions of intact retina around the lesions. Although these “reactivated” neurons respond to visual stimuli, quantitative studies of their response characteristics have not been attempted. Thus, it is not known whether these neurons have normal or abnormal features that could contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 52 publications
(81 reference statements)
8
87
4
Order By: Relevance
“…In summary, both cat and monkey studies provide evidence for retinotopic reorganization as a result of retinal deafferentation (Kaas et al, 1990;Heinen & Skavenski, 1991;Gilbert & Wiesel, 1992;Chino et al, 1992Chino et al, , 1995Darian-Smith & Gilbert, 1994, 1995Calford et al, 2000). Extensive reviews on cortical plasticity of sensory and motor organization can be found in Chino (1995), Gilbert (1998), and Kaas and Collins (2003).…”
Section: Animal Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…In summary, both cat and monkey studies provide evidence for retinotopic reorganization as a result of retinal deafferentation (Kaas et al, 1990;Heinen & Skavenski, 1991;Gilbert & Wiesel, 1992;Chino et al, 1992Chino et al, , 1995Darian-Smith & Gilbert, 1994, 1995Calford et al, 2000). Extensive reviews on cortical plasticity of sensory and motor organization can be found in Chino (1995), Gilbert (1998), and Kaas and Collins (2003).…”
Section: Animal Studiesmentioning
confidence: 96%
“…Cat and monkey studies have shown that reorganization in adult mammalian visual cortex occurs following visual field loss (Kaas et al, 1990;Heinen & Skavenski, 1991;Gilbert & Wiesel, 1992;Chino et al, 1992Chino et al, , 1995Darian-Smith & Gilbert, 1994, 1995Calford et al, 2000). Prior to these studies, prevailing wisdom held that connections along the retinocortical visual pathways are very rigid following a developmental critical period (weeks old) (see Boothe et al, 1985 for a review).…”
Section: Animal Studiesmentioning
confidence: 99%
“…Selective somatosensory deafferentation leads to extensive reorganization in both the thalamus and cortex (Garraghty and Kaas, 1991;Nicolelis et al, 1991;Pettit and Schwark, 1993;Faggin et al, 1997;Jones, 2000). In contrast, localized retinal lesions produce dramatic changes in visual topography and receptive field size in V1 (Heinen and Skavenski, 1991;Gilbert and Wiesel, 1992;Chino et al, 1995) but few changes in the LGN (Gilbert and Wiesel, 1992;Darian-Smith and Gilbert, 1995). Stimulus differences may also explain why pronounced effects are not seen in primary visual cortex.…”
Section: Comparison Between the Visual System And Other Sensory Systemsmentioning
confidence: 99%
“…Plasticity in adult visual cortex has been shown in response to localized deafferentation by retinal lesioning (Chino et al 1992(Chino et al , 1995Gilbert and Wiesel 1992;Heinen and Skavenski 1991;Kaas et al 1990). Yet few studies have addressed how neuronal properties in adult V1 change as a consequence of training.…”
Section: Introductionmentioning
confidence: 99%